Uzbekistan 2018 Public Expenditure and Financial Accountability Performance Assessment Report - World Bank (World Bank, Washington, DC, 2019)
The main purpose of the 2018 public expenditure and financial accountability (PEFA) assessment is to provide the Government of Uzbekistan and its development partners with an objective up-to-date diagnostic of the national-level public financial management performance based on the latest internationally recognized PEFA methodology. The 2018 PEFA assessment is intended to provide an update of progress in Public Finance Management (PFM) since the last PEFA in 2012, but also establish a new baseline using the 2016 PEFA methodology. This methodology identifies the seven pillars of performance that are essential for an open and orderly PFM system. These include budget reliability, transparency of public finances, management of assets and liabilities, policy-based fiscal strategy and budgeting, predictability and control in budget execution, accounting and reporting, and external scrutiny and audit. The assessment process seeks to build a shared understanding of PFM performance and those dimensions that require improvement. The results of the assessment will assist the government in monitoring the implementation of Uzbekistan’s Public Financial Management Reform Strategy to achieve long-term sustainability.